Compound‐heterozygous GRIN2A null variants associated with severe developmental and epileptic encephalopathy. Issue 10 (30th August 2022) - Strehlow, Vincent; Rieubland, Claudine; Gallati, Sabina; Kim, Sukhan; Myers, Scott J.; Peterson, Vincent; Ramsey, Amy J.; Teuscher, Daniel D.; Traynelis, Stephen F.; Lemke, Johannes R.
Abstract: We report on an 8‐year‐old girl with severe developmental and epileptic encephalopathy due to the compound heterozygous null variants p.(Gln661*) and p.(Leu830Pro fs *2) in GRIN2A resulting in a knockout of the human GluN2A subunit of the N‐methyl‐D‐aspartate receptor. Both parents had less severe GRIN2A ‐related phenotypes and were heterozygous carriers of the respective null variant. Functional investigations of both variants suggested a loss‐of‐function effect. This is the first description of an autosomal recessive, biallelic type of GRIN2A ‐related disorder. Nonetheless, there are marked parallels to two previously published families with severe epileptic encephalopathy due to homozygous null variants in GRIN1 as well as various knockout animal models. Compared to heterozygous null variants, biallelic knockout of either GluN1 or GluN2A is associated with markedly more severe phenotypes in both humans and mice. Furthermore, recent findings enable a potential precision medicine approach targeting GRIN ‐related disorders due to null variants.